Intraventricular hemorrhage and its fibrinolytic treatment: literature review - Dzenis, Yuris L.; Stirans, Karlis Y. (Ukrainian Neurosurgical Journal, 2017)
The review is dedicated to intraventricular hemorrhage (IVH) and its treatment with topical intraventricular fibrinolysis (IVF). We evaluated many clinical factors typical for IVH: etiology, classifications, symptoms, diagnostics, qualitative and quantitative results and in case of re-bleeding the breakdown site where blood enters venricular system. The paper considers main elements of IVF evaluated, namely indications, external ventricular drain (EVD) techniques, fibrinolytic administration through the drainage catheter vs intratecali, fibrinolytic dosage used (urokinase, tissue plasminogen activator). The paper describes the results following IVH: mortality, main complications (re-bleeding, ventriculitis, shunt-dependence ect) and functional outcome. This article reviews the general points associated with IVH and its treatment with topical IVF.